Managing strategic alignment using the balanced scorecard: A Malaysian company’s experience - Ayoup, Hazeline; Omar, Normah; Abdul Rahman, Ibrahim Kamal (2015)
The main purpose of this study is to explore the used of the Balanced Scorecard (BSC) as a strategic alignment tool in a large Malaysian organization using the qualitative case study approach.This study indicates that the BSC, through its performance indicators helps to partially improve the alignment of a company’s strategic objectives and strategies between the top management and the lower management levels.It also helps to align the various divisions in the organizations at the strategic level.However, full alignment is still a long way to achieve.This study highlighted the importance of awareness, common understanding and systematic alignment process in managing the alignment process and issue faces by the management in the process.